2017
DOI: 10.1097/mib.0000000000001140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Acceptability and Perceived Clinical Utility of Monitoring Tools

Abstract: Among the IBD monitoring tools, endoscopy demonstrated the lowest acceptability supporting the development of alternative modalities. Patients' information and examination conditions should be improved to ensure proper monitoring adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 49 publications
4
121
1
1
Order By: Relevance
“…Accordingly, GIUS was ranked as the preferred tool for monitoring by the evaluated IBD cohort. Previous studies in IBD have shown that noninvasive tests are preferred to invasive tests, such as colonoscopy, because of factors such as the need for bowel preparation and discomfort of the test . In this study, GIUS was preferred over all other tests, including noninvasive options such as blood collection and stool sampling.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Accordingly, GIUS was ranked as the preferred tool for monitoring by the evaluated IBD cohort. Previous studies in IBD have shown that noninvasive tests are preferred to invasive tests, such as colonoscopy, because of factors such as the need for bowel preparation and discomfort of the test . In this study, GIUS was preferred over all other tests, including noninvasive options such as blood collection and stool sampling.…”
Section: Discussionmentioning
confidence: 97%
“…As opposed to previous studies assessing acceptability of IBD tools, this study also looked at the impact on disease‐related knowledge, and to the author's knowledge, this is the first study performed in Australia to evaluate GIUS in this manner. Although there is no validated tool for evaluating patient perceptions of diagnostic tests, a VAS was used, which was similar to previous studies . Administration of a questionnaire soon after a test also raises the possibility of recall bias in reporting comparative acceptability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This perception, however, may be inaccurate as a flexible sigmoidoscopy is not risk free, requires preparation, is typically performed with sedation, and may not be accepted by all patients. In a nationwide French study assessing the acceptability of monitoring tools in IBD, flexible sigmoidoscopy was considered the least acceptable monitoring tool by patients with UC compared to venipuncture, FC, and ileocolonoscopy . Our findings suggest that POCUS can be effectively used as an alternative tool to monitor disease activity in patients with UC with disease extending beyond the rectum.…”
Section: Discussionmentioning
confidence: 70%